Molecular characterization of genes encoding AmpC beta-lactamases in clinical isolates of Pseudomonas and Acinetobacter species - Sana Jamali, Mohd. Shahid, Sobia Farrukh, Anuradha Singh, Haris M. Khan (Journal of Applied Pharmaceutical Science, 2015)
Emergence of AmpC beta-lactamases in isolates of Pseudomonas and Acinetobacter species, is a threatening condition as they mediate resistance to a wide variety of β-lactam drugs, including α-methoxy-β-lactams, such as cefoxitin, narrow-, expanded- and broad-spectrum cephalosporins, aztreonam and are poorly inhibited by β-lactam inhibitor combinations. The present study was conducted to determine the occurrence of blaampC genes in these pathogenic non-fermenters for their rapid and accurate detection. Monoplex PCR was done to detect blaampC genes in 40 non-duplicate clinical Pseudomonas and Acinetobacter isolates, that were found resistant to any of the third-generation cephalosporin and cefoxitin. Multiplex PCR assay was carried out to identify family-specific AmpC beta-lactamase genes within Pseudomonas and Acinetobacter spp. PCR detected ¬blaampC in 43.24% of Pseudomonas and 33.33% of Acinetobacter isolates. Overall 42.50% of the total isolates were found to harbour blaampC genes by PCR. By multiplex PCR, total eight (20%) isolates yielded a positive amplicon with AmpC-specific primers. High prevalence of blaampC genes in cefoxitin-resistant isolates of Pseudomonas and Acinetobacter isolates emphasizes that molecular detection methods should be carried out to know the exact prevalence of beta-lactamases.
Keywords: blaampC, Pseudomonas, Acinetobacter.